2021
DOI: 10.21203/rs.3.rs-744730/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autism and Inner Speech: A Computational Model of Language Functions in Autistic Flexible Behaviour

Abstract: Experimental and computational studies propose that inner speech boosts categorisation skills and executive functions, making human behaviour more focused and flexible. In addition, many clinical studies highlight a relationship between poor inner-speech and an executive impairment in autism spectrum condition (ASC), but contrasting findings are reported. Here we investigate the latter issue through a previously implemented and validated computational model of the Wisconsin Cards Sorting Tests.In particular, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…For example, recent computational work with a model reproducing the effects of the Wisconsin Card Sorting test showed that inner speech strongly enhanced cognitive flexibility [173]. Consistently, the reduced use of IS could explain some impairments in children and elderly autistic people [174].…”
Section: Abstract Concepts and Inner Speechmentioning
confidence: 92%
“…For example, recent computational work with a model reproducing the effects of the Wisconsin Card Sorting test showed that inner speech strongly enhanced cognitive flexibility [173]. Consistently, the reduced use of IS could explain some impairments in children and elderly autistic people [174].…”
Section: Abstract Concepts and Inner Speechmentioning
confidence: 92%
“…Compatible neural evidence shows that during abstract thought, neural areas linked to inner speech are engaged (Berkovich-Ohana et al, 2020). There is also some evidence from autistic spectrum condition (ASC) individuals who scarcely make use of inner speech (Granato et al, 2021). ASC individuals have some impairments during categorization and prototype extraction (e.g., Church et al, 2015), but the evidence that they have more difficulties in processing of abstract compared to concrete concepts is scattered and controversial results are present (e.g., Eskes et al, 1990).…”
Section: Metacognition and Inner Speech For Abstract Conceptsmentioning
confidence: 99%